Elevated Temperature Performance of a Novel Eco-Friendly Cementitious Material - Zghair, Luma A. G.; Yousif, Mohammad Z.; Al-Hamd, Rwayda Kh. S. (Engineering, Technology & Applied Science Research, 2025)
This study presents the development of a novel environmentally friendly cementitious material and examines its behavior at elevated temperatures. Ceramic Waste Powder (CWP) and Fly Ash (FA) were utilized as substitutes for cement at a concentration of 10%. Four distinct mix designs were formulated and evaluated. The flow table test was implemented to study the workability of the mortar, while 120 cubes and 39 specimens were shaped into briquettes. The specimens’ compressive strength, mass loss, and tensile strength were analyzed after exposure to temperatures ranging from 150 °C to 700 °C, deploying Field Emission Scanning Electron Microscopy (FESEM) testing. The research findings indicate that CWP can function as a sustainable material in construction, diminishing the carbon footprint of construction materials and alleviating the environmental damage resulting from CWP disposal in landfills. Furthermore, it was found that FA can be combined with pulverized ceramic to substitute cement, resulting in a sustainable cement mortar. It was concluded that sustainable mortar production was attained while substituting 20% of cement with alternative materials.